Is the old Age a desease? Perceptions of health professionals - Gelehrter da Costa Lopes, Ruth (2015)
Human longevity is a recurring theme that makes us turn our attention to the elderly with chronic diseases. The study aimed to understand the professional context that gives visibility to the adult who is sick, which unveiled this paradigm in the light of the review of 20 professionals working with this population. The research focused on the multidisciplinary team of a company in the city of São Paulo, which develops a care management program for users of prepaid health plans. Methodology of quantitative and qualitative research, based on content analysis was used. It was noted that most of the subjects is the area of nursing and its proposed intervention focuses on the quality of life of patients. Although there is an understanding of what is old age, health-related illness is an issue that needs more attention in the curriculum.